Schistosomiasis messaging in endemic communities: Lessons and implications for interventions from rural Uganda, a rapid ethnographic assessment study. - Agnes Ssali (Public Library of Science (PLoS), 2021)
Background Over 240 million people are infected with schistosomiasis, the majority in sub-Saharan Africa. In Uganda, high infection rates exist in communities on the shores of Lake Victoria. Praziquantel mass drug administration (MDA) delivered by village health teams is the mainstay of schistosomiasis control. However, treatment uptake remains suboptimal, with many people unaware of treatment or thinking it is only for children. Furthermore, people are often rapidly reinfected post-treatment due to continued exposure. In three Schistosoma mansoni high endemicity lake-shore communities in Mayuge district, Eastern Uganda, we investigated the sources of schistosomiasis information, remembered content of information, and the perception of information and related practices towards the control of schistosomiasis. Methods and principal findings Data were collected from September 2017 to March 2018 using a rapid ethnographic assessment that included transect walks, observations, individual in-depth interviews and focus group discussions. Data were analysed thematically using iterative categorisation. We found that the main sources of schistosomiasis information included health workers at government facilities, village health teams, teachers, and radio programmes produced by the Ministry of Health. These messages described the symptoms of schistosomiasis, but did not mention the side effects of praziquantel treatment. Despite this messaging, the main cause of the disease and transmission was unclear to most participants. The translation of schistosomiasis on the radio into the local language 'ekidada'-meaning swollen stomach-increased, rather than reduced, confusion about the cause(s) of schistosomiasis, due to believed links between ekidada and witchcraft, and prompted a reluctance to engage with treatment or preventative efforts. Conclusion and significance This study highlights gaps in schistosomiasis messaging. We recommend MDA is complemented by effective, evidence-based messaging on schistosomiasis transmission, prevention, and treatment, that is sensitive to local language and context issues, resulting in clear, concise, and consistent messages, to increase effectiveness.